Salinity matters the most: How environmental factors shape the diversity and structure of cyanobacterial mat communities in high altitude arid ecosystems - Sandzewicz, Małgorzata; Khomutovska, Nataliia; Łach, Łukasz; Kwiatowski, Jan; Niyatbekov, Toirbek; Suska-Malawska, Małgorzata; Jasser, Iwona (Frontiers in Microbiology, 2023)
Microbial mats are complex communities of benthic microorganisms that occur at the soil-water interphase in lakes’ shores, streams, and ponds. In the cold, mountainous desert of Eastern Pamir (Tajikistan), where scarce water bodies are influenced by extreme environmental conditions, photosynthetic cyanobacteria form diverse mats. The mats are characterized by different morphology and thickness. Their habitats exhibit a wide range of conditions; from oligosaline to hypersaline, oligotrophic to hypertrophic, and from cold ponds to hot springs. The aim of the present study was to reveal the taxonomic composition and structure of these mats and to examine which environmental factors influence them. Fifty-one mats were collected from small water bodies around Bulunkul, Karakul, and Rangkul Lakes in 2015 and 2017. The physical and chemical properties of the water were measured in situ, while the concentration of nutrients was analyzed ex-situ. To reveal the taxonomic composition of the mats, the hypervariable V3-V4 region of the 16S rRNA gene was examined using NGS technology. The results of the bioinformatic analyses were compared with microscopic observations. They showed that Cyanobacteria was the dominant phylum, constituting on average 35% of bacterial ASVs, followed by Proteobacteria (28%), Bacteroidota (11%) and Firmicutes (9%). Synechococcales, Oscillatoriales and Nostocales orders prevailed in Oxyphotobacteria, with a low contribution of Chroococcales, Gloeobacterales and Chroococcidiopsidales. Occasionally the non-photosynthetic Vampirivibrionia (Melainabacteria) and Sericytochromatia from sister clades to Oxyphotobacteria were noted in the samples. Moreover, there was a high percentage of unidentified cyanobacterial sequences, as well as the recently described Hillbrichtia pamiria gen. et sp. nov., present in one of the samples. The results suggest that the studied communities possibly host more novel and endemic species. Among the environmental factors, salinity, followed by Na, K and C concentration, influence the composition and structure of Oxyphotobacteria on different taxonomic levels the most. Salinity also correlated positively with an abundance of all bacterial ASVs. Overall, the microenvironmental factors, i.e. the conditions in each of the reservoirs seemed to have a larger impact on the diversity of microbial mats in Pamir than the “subregional” factors, related to altitude, mean annual air temperature and distance between these subregions.